Association between Depression and Diabetes: A Literature Review - Manasi Behera; Tapaswini Mishra; Dipti Mohapatra; Arati Meher (Current Overview on Disease and Health Research Vol. 1, 2022)
Introduction: Diabetes mellitus is a major health problem not only in developing countries but also indeveloped countries. Depression and diabetes are two major health disorders that arebidirectionally associated. Some studies show strong relationship between diabetes anddepression. Sometimes diabetes and depression combined increases the mortality and morbidity rate. Early identification and proper treatment of depression can improve the quality of life. Conclusion: Depression and diabetes are associated bidirectionally. Both have major impact on health and economic outcomes. Improvement in depression score is correlated with improvement in glycaemic control. Concerning awareness and identifying these conditions early improves the outcomes of depression and diabetes and ultimately improve health outcomes and quality of life.